Studi Evaluasi Penguatan Pendidikan Karakter Berbasis Kearifan Lokal pada Siswa SMP Harapan Nusantara Denpasar - Uttami Wijayanti; Kadek Rihendra Dantes; Basilius Redan Werang (Jurnal Administrasi Pendidikan Indonesia, 2023)
This study aims to evaluate the strengthening of character education based on local wisdom for students of SMP Harapan Nusantara Denpasar. This research is ex-post facto research with CIPP design (Context, Input, Process, Product). The population used in this study were students of SMP Harapan Nusantara Denpasar class VII–IX with 346 students. While the sample used in this study was 186 students. The data collection method used in this study was a questionnaire using a Likert scale of 1-5. The data analysis method used in this study is a quantitative descriptive analysis method. To determine the effectiveness of the raw score data transformed into Z-scores then into T-Scores then verified into the Glickman Quadrant. Based on the research that has been done, the results show that: 1) The effectiveness of strengthening local wisdom-based character education for Harapan Nusantara Denpasar Middle School students in terms of the context obtained effective results (+), 2) The effectiveness of strengthening local wisdom-based character education for Harapan Nusantara Middle School students Denpasar in terms of input obtained effective results (+), 3) The effectiveness of strengthening local wisdom-based character education for Harapan Nusantara Denpasar Middle School students in terms of the process obtained less effective results (-), 4) The effectiveness of strengthening local wisdom-based character education for students Harapan Nusantara Middle School Denpasar in terms of product obtained effective results (+), 5) The results of a joint evaluation of strengthening local wisdom-based character education for Harapan Nusantara Denpasar Middle School students in terms of context, input, process and product obtained effective results (+ + - +).